Galveston Orientation & Amnesia Test (GOAT) Score to Assess Degree of Severity in Mild Brain Injury - Zieky Yohansyah; Sahat Edison Sitorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2019)
ABSTRACT Introduction. Most of the minor brain injuries will heal as usual, but around 10-15% even 58% experience a continuous or chronic disorder known as post-traumatic syndrome. Post traumatic syndrome has manifested in the first 7 days where the quality of life of patients has decreased significantly. This study aimed to assess post traumatic amnesia in minor traumatic brain injuries in Emergency, Inpatient, and Outpatient RSUP. Moh. Hoesin Palembang using GOAT to determine the classification of minor brain injuries based on post traumatic amnesia and determine the prognosis of mild traumatic brain injury according to the presence or absence of post-traumatic syndrome. Methods. This research is an analytic survey with cross sectional approach. The subjects of this study were patients who were admitted and treated at the Emergency Department, Inpatient Installation, and Outpatient Installation (Polyclinic) at the RSUP dr. Mohammad Hoesin Palembang with mild traumatic brain injury and met the inclusion criteria. Inclusion criteria were patients who present with mild brain injury (GCS EMV score 13-15), age â‰¥ 15 years, the time of the event lasts longer â‰¤ 24 hours, agreeing and signing informed consent Results. Amnesia assessment uses the GOAT (Galveston Orientation and Amnesia Test) which is divided into three categories, namely PTA free if results> 75, and still in amnesia period if results <66 and 66-75 are doubtful. Based on GOAT assessment the number of Amnesia respondents was 23 people (42.6%) with an average GOAT score or score of 67.6. Conclusion. There is a significant relationship between the incidence of amnesia and post-traumatic syndrome using the GOAT Score assessment.